PEMANFAATAN BERBAGAI JENIS PUPUK BERBAHAN LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN TANAMAN - Subhaktiyasa Putu Gede; Putri Sumaryani N. (FPMIPA IKIP PGRI Bali, 2020)
The research objective was to describe the types of household waste that can be used as fertilizer in increasing plant growth. This type of research is descriptive research with literature study by discussing household waste that can be used as organic fertilizer. The independent variable in this study is the type of fertilizer from household waste, the dependent variable in this study is plant growth. In this study, the operational variable is plant vegetative growth. In plant growth there will be an increase in the volume, number, shape and size of the vegetative organs. Meanwhile, vegetative growth of plants starts from the growth of roots, stems and leaves. In this phase, plants need a lot of food reserves which will be converted into energy for growth. Waste that can be used as fertilizer can be fertilized into solid or liquid organic fertilizers to help plant growth. The waste includes, among others, bagasse, duck egg shells, chicken egg shells, peanut shells, tea dregs, coconut dregs, green bean sprouts.